Resilient Cloud Architectures for HRIS and ERP Systems - Sakshi Godse; Ritu Jain; Dragan Stankovski (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
As organizations increasingly migrate their human resource information systems (HRIS) and enterprise resource planning (ERP) systems to the cloud, ensuring the resilience and reliability of these critical applications becomes paramount. This research paper explores the key considerations, architectural patterns, and best practices for designing and implementing resilient cloud architectures for HRIS and ERP systems. By analyzing industry case studies, emerging technologies, and innovative deployment strategies, we propose a comprehensive framework for building robust and fault-tolerant cloud environments that can withstand disruptions and ensure business continuity. Our findings highlight the importance of multi-cloud architectures, event-driven monitoring, and automated disaster recovery mechanisms in achieving high levels of resilience. The proposed framework provides valuable insights for organizations seeking to optimize their cloud-based HRIS and ERP deployments while minimizing downtime and data loss.